2021
DOI: 10.1038/s41598-021-94372-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic traits mediate guilt-related anterior midcingulate activity under authority pressure

Abstract: Coercive power has different effects on individuals, and which were unable to be fully addressed in Milgram’s famous studies on obedience to authority. While some individuals exhibited high levels of guilt-related anxiety and refused orders to harm, others followed coercive orders throughout the whole event. The lack of guilt is a well-known characteristic of psychopathy, and recent evidence portrays psychopathic personalities on a continuum of clustered traits, while being pervasive in a significant proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Cathodal tDCS accelerated harming RTs, whereas anodal tDCS did not exert such an effect. The present findings replicated a previous study (Cheng et al, 2021 ), regarding longer RTs and more self‐reported violation of subjects' own will for harming than helping. However, as opposed to our hypothesis, enhancing a sense of agency by applying anodal tDCS to the rTPJ did not change behaviors under authority pressure.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Cathodal tDCS accelerated harming RTs, whereas anodal tDCS did not exert such an effect. The present findings replicated a previous study (Cheng et al, 2021 ), regarding longer RTs and more self‐reported violation of subjects' own will for harming than helping. However, as opposed to our hypothesis, enhancing a sense of agency by applying anodal tDCS to the rTPJ did not change behaviors under authority pressure.…”
Section: Discussionsupporting
confidence: 91%
“…A virtual obedience paradigm inspired by prior studies on obedience to authority (Caspar et al, 2016 ; Caspar et al, 2018 ; Caspar, Ioumpa, et al, 2020 ; Caspar, Lo Bue, et al, 2020 ; Cheng et al, 2021 ), in which an experimenter ordered a subject to inflict harm to a third party, was designed to measure participants' behavior under authority power (Figure 1 ). During fMRI scanning, participants watching the first image of a mini‐clip of a social interaction were forced (ordered via textual instructions) to press a button in order to initiate successive actions that carried different consequences, including harming, neutral, and helping actions, along with visual feedback of each scenario.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychopathy is associated with a cluster of traits including manipulativeness, dishonesty, narcissism, superficial charm, reckless risk-taking, impulsive antisocial behavior, and arguably one of the most characteristic traits, lack of guilt [ 51 ]. Psychopaths show significant impairment in the orbital frontal cortex (OFC) and the prefrontal cortex, which are most commonly recognized as the most crucial brain structures to be compromised in violent and antisocial populations [ 52 , 53 ].…”
Section: Guiltmentioning
confidence: 99%